"Some of us, we don't know where we're going to be tomorrow." Contextual factors affecting PrEP use and adherence among a diverse sample of transgender women in San Francisco. Issue 5 (3rd May 2020) - Cahill, Sean R.; Keatley, JoAnne; Wade Taylor, S.; Sevelius, Jae; Elsesser, Steven A.; Geffen, Sophia R.; Wang, Tim; Mayer, Kenneth H.
ABSTRACT: Transgender women (TW) are disproportionately affected by HIV. Antiretroviral pre-exposure prophylaxis (PrEP) can reduce TW's vulnerability to HIV, but PrEP uptake has been limited among TW. To explore barriers to PrEP uptake, the study team conducted two semi-structured focus groups with TW in San Francisco at risk for HIV acquisition. A within-case, across-case approach was used to code and analyze emerging themes. Focus group participants were racially and ethnically diverse. A few participants in both groups had heard of PrEP, but some had not. Several said that their health care providers had not told them about PrEP. Participants in both groups had questions about side effects. They expressed medical mistrust and said poverty is an important context for their lives. They described a need for gender affirming health care services and raised concerns about interactions of PrEP with feminizing hormones. Information about side effects and interactions between gender affirming hormones and PrEP need to be explicitly addressed in PrEP education campaigns focusing on TW. Health care institutions and health departments should train clinical staff how to provide affirming care. Gender identity nondiscrimination laws and policies could improve transgender people's ability to earn a living and access health care.